Pengaruh Gaya Kepemimpinan terhadap Turnover Intention dengan Kepuasan Kerja sebagai Variabel Mediasi pada Karyawan Pressed Cafe And Mylk Canggu - Ni Komang Tia Sugiartini; Ni Nyoman Sudiyani; Putu Gede Denny Herlambang (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
A company's success in achieving its organizational goals is largely determined by the quality of its human resources. A common challenge faced by companies is high employee turnover intention, which can lead to increased recruitment costs, reduced productivity, and disruptions to operational continuity. Leadership style is considered a factor influencing turnover intention, either directly or through job satisfaction as a mediating variable. This study aims to analyze the impact of leadership style on turnover intention, with job satisfaction serving as a mediating variable, among employees at Pressed Cafe and Mylk Canggu. A quantitative approach was employed, utilizing descriptive and associative research designs. The study population consisted of 35 employees, all of whom were included in the sample using a saturated sampling technique. Data were collected through observation, interviews, and questionnaires. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software, involving outer model, inner model, and bootstrapping tests. The results indicate that leadership style has a negative but insignificant effect on turnover intention. Conversely, leadership style has a positive and significant effect on job satisfaction, while job satisfaction has a negative and significant effect on turnover intention. Furthermore, job satisfaction was found to mediate the influence of leadership style on turnover intention through an "indirect-only mediation" mechanism. These findings suggest that improving leadership style will be more effective in reducing turnover intention if it first succeeds in enhancing employee job satisfaction.